Energy efficiency, carbon emissions, and measures towards their improvement in the food and beverage sector for six European countries. (1st June 2016) - Meyers, Steven; Schmitt, Bastian; Chester-Jones, Mae; Sturm, Barbara
Abstract: Basic and detailed audits of small and medium sized food and beverage enterprises were conducted in six European Union countries to determine product specific energy consumption and measures to reduce energy use and carbon emissions. Collected results showed that the companies' products had similar specific energy consumption as prior studies, but due to no standard metrics, the range was rather large. Auditors primarily recommended energy savings measures (process optimization and heat recovery), due to their low payback periods. Lower carbon energy sources were also recommended (solar thermal and combined heat/power), but often at higher costs, supported through government incentive programs. Through these measures, energy savings of up to 45% and carbon to 30% (∼30, 000 t CO2 equivalent in the audited companies) were possible, dependent on the type, size of company, and fuel choice. Typically, very small companies and those using coal showed the greatest margin for improvement, though it varied greatly depending on the type of product produced and the installed heating and cooling equipment. Auditors noted significant barriers toward the implementation of measures, e.g. companies found the costs too high, did not know of efficient technologies and their performance, or did not have managerial support to implement efficiency measures. Highlights: The Food and Beverage sector in Europe was assessed for carbon reduction potential. Significant emission reductions can be achieved by energy efficiency and renewables. The Bakery and Meat branches can reduce energy consumption by 30–40%. Small and coal burning companies have the greatest potential for emission reduction. Financial barriers remain the hardest obstacle to realize reduction potential.